Effects of colonic fermentation on the stability of fresh and black onion bioactives. Issue 8 (18th March 2022) - Moreno-Ortega, Alicia; Di Pede, Giuseppe; Mena, Pedro; Calani, Luca; Del Rio, Daniele; Moreno-Rojas, José Manuel; Pereira-Caro, Gema
Abstract : The health properties related to onion intake are attributed mainly to the presence of bioactive compounds, particularly phenolic and organosulfur compounds (OSCs). Abstract : The health properties related to onion intake are attributed mainly to the presence of bioactive compounds, particularly phenolic and organosulfur compounds (OSCs). The aim of this study was to investigate, for the first time, the effect of an in vitro colonic fermentation on the stability of phenolic and OSCs of fresh and black onion by ultra-high-performance liquid chromatography coupled with mass spectrometry with a linear ion trap (UHPLC-LIT-MS). Throughout colonic fermentation, fresh onion showed an increase in the total phenolic content of 45%, mainly due to an increase in the content of the flavonoid family, while the OSCs remained stable along the fermentation. Black onion presented a different behaviour, showing significant decreases in total (poly)phenol and OSC content, 22 and 48%, respectively. The main compounds found after the in vitro colonic fermentation of fresh onion were isorhamnetin (141 μmol L −1 ), quercetin (95 μmol L −1 ), 3, 4-dihydroxybenzoic acid (53 μmol L −1 ), methionine sulfoxide (100 μmol L −1 ) and S -allylcysteine (SAC) (21.7 μmol L −1 ), whereas 3, 4-dihydroxybenzoic acid (70 μmol L −1 ), 4-hydroxyphenylacetic acid (68 μmol L −1 ), methionine sulfoxide (82 μmol L −1 ) and S -propylmercapto-l -cysteine (SPMC) (10.1 μmol L −1 ) accounted for the highest concentrations of phenolics and OSCs in fermented black onion. These compounds, presumably present for their absorption and action at the colonic level, could be related to the health benefits of regular consumption of fresh and black onion.